2011
DOI: 10.3363/prb.25.18
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Phosphate From Unused Resources

Abstract: The recovery of aqueous phosphate from a model solution consisting of NH 4 + , NO 2 and NO 3-, which are contained in a surplus that phosphate in rivers in Tokushima Prefecture, Japan, using boehmite together with the elution behaviors of phosphate from dephosphorization slag using various eluates were examined. The recovery of aqueous phosphate using boehmite was not influenced by the coexistence of those nitrogen-containing contaminants under various pH conditions. For the elution behaviors of phosphate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…To confirm the element distribution with the exception of carbon species, the solid was also analyzed using an electron probe micro analyzer (EPMA; EDAX, Phoenix). To examine the removal of aqueous Fe 3+ with CaHAp, an aqueous solution (100 ml), to which a known quantity of Fe(NO 3 ) 3 . 9H 2 O (Wako) had been added, was stirred at 120 rpm in a constant temperature bath at 293 K for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To confirm the element distribution with the exception of carbon species, the solid was also analyzed using an electron probe micro analyzer (EPMA; EDAX, Phoenix). To examine the removal of aqueous Fe 3+ with CaHAp, an aqueous solution (100 ml), to which a known quantity of Fe(NO 3 ) 3 . 9H 2 O (Wako) had been added, was stirred at 120 rpm in a constant temperature bath at 293 K for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the content of the various elements in the brown powder, 0.14 g of the powder was dissolved in aq. HNO 3 . Since 93% of the brown powder could be dissolved in aq.…”
Section: Effect Of the Pretreatment Of The Slag On The Elution Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results shown by Miki et al, 2) the solubility of C 2 S is much greater than that of C 3 P in sea water, and the solubility of both phases decreases with an increase in pH. S. Sugiyama et al 3,4) has investigated the elution of phosphorus from industrial steelmaking slag and revealed that phosphorus was able to be easily eluted using 1 mol/L-HNO 3 solution. However, by their condition, elution rates of Fe 3+ was comparably high as that of PO 4 3-, and the separation of Fe 3+ in the solution was necessary to recover phosphorus.…”
Section: Introductionmentioning
confidence: 99%